Investigating the Relationship Between Insulin-Like Growth Factor-I and Thyroid Hormones in Thyroid Disorder Patients - Asaad, Aveen M.; Kakey, Ismail S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The insulin-like growth factor I (IGF-I) system plays a pivotal role in endocrine regulation, metabolism, and cellular growth; however, its interaction with thyroid hormones in the context of thyroid dysfunction remains insufficiently understood. This study aimed to investigate the correlations between IGF-I and thyroid hormones, TSH, T3, and T4, in females diagnosed with thyroid disorders. After removing 15 women due to pregnancy or medication use, 160 women from the Koya district were assessed. Serum levels of IGF-I and thyroid hormones were measured using the COBAS e411 analyzer, and body mass index (BMI) was also recorded. Statistical analysis was conducted using SPSS 25, employing Kruskal-Wallis ANOVA and Spearman correlation for thyroid groups: hyperthyroid, hypothyroid, and euthyroid. The results demonstrated significant variation in IGF-I levels across thyroid conditions. IGF-I was markedly elevated in hyperthyroid individuals and showed a moderate inverse correlation with TSH, along with a positive correlation with T3 and T4. Hypothyroid individuals exhibited significantly lower IGF-I levels, suggesting a regulatory role of IGF-I in thyroid hormone dynamics. Additionally, BMI varied significantly across groups (p < 0.001), with the highest values are observed in hypothyroid participants, supporting the metabolic implications of thyroid dysfunction and its association with IGF-I. The study concludes that IGF-I could serve as a valuable adjunct biomarker in the assessment of thyroid disorders, particularly in ambiguous or subclinical cases. Incorporating IGF-I into routine thyroid evaluation may enhance early detection, risk stratification, and individualized management strategies, contributing to more precise and effective endocrine care.